Angiostrongylus cantonensis infection mimicking a spinal cord tumor - Petjom S. (2014)
Angiostrongylus cantonensis is the most common cause of eosinophilic meningitis and meningoencephalitis. Almost all cases are self-limiting and are diagnosed by cerebrospinal fluid eosinophilia and enzyme-linked immunosorbent assay; pathology reports are restricted to postmortem samples from lethal cases. We report on what we believe is the first case of A. cantonensis infection diagnosed by biopsy in a living patient. The spinal cord was biopsied because of the unusual clinical presentation of a myelopathy without meningeal symptoms, together with a mass lesion that was clinically and radiologically diagnosed as a spinal cord tumor.